Treatment of severe chronic ocular graft-versus-host disease using 100% autologous serum eye drops from a sealed manufacturing system: a retrospective cohort study. Issue 3 (6th June 2016) - Tahmaz, Volkan; Gehlsen, Uta; Sauerbier, Laura; Holtick, Udo; Engel, Lisa; Radojska, Stela; Petrescu-Jipa, Viorica-Maria; Scheid, Christof; Hallek, Michael; Gathof, Birgit; Cursiefen, Claus; Steven, Philipp
Abstract : Background/Aims: To analyse patients with chronic ocular graft-versus-host disease (GvHD) under treatment with 100% autologous serum eye drops from a sealed manufacturing system. Methods: 17 patients with chronic ocular GvHD received 100% autologous serum eye drops from single use vials manufactured in a sealed system. Retrospective analysis included visual acuity, corneal staining, frequency of artificial tears, ocular symptoms by means of a questionnaire and information on subjective side effects and cost compensation. Results: Data of prior to autologous serum eye drops therapy and at a 6-month follow-up were obtained. They demonstrated a significant increase in visual acuity (logMAR oculus dexter/right eye (OD) 0.5±0.32 to 0.4±0.3; oculus sinister/left eye (OS) 0.6±0.35 to 0.3±0.35; p=0.177/0.003) and significant improvement in corneal staining (Oxford grading scheme: OD from 3±1.03 to 2±1.43, OS from 4±1.0 to 2±1.09, p=0.004/0.001) and ocular symptoms (ocular surface disease index: 88±20.59 to 63±22.77; p=0.02). Frequency of artificial tears was reduced and no side effects were reported. Patient satisfaction was 100%, and cost compensation by health insurance reached 80%. Conclusions: 100% autologous serum eye drops using a sealed manufacturing system were efficient in improving the ocular surface, patient symptoms and visual acuity without side effects. It seems to be safe to use 100% autologous serum despite earlier suspicions regarding immune complex accumulations and exacerbation of ocular surface inflammation. The potential effects of serum levels of systemic immunosuppressives through readministration onto the ocular surface need to be elucidated.